METODE TIKRAR DALAM TAHFIDZ AL-QUR’AN: STUDI KASUS DI PONDOK PESANTREN TAKHASSUS AL-QUR’AN - Ikhwanuddin, Muhammad (ILJ: Islamic Learning Journal, 2023)
This research was conducted at the Takhassus Al-Qur'an Pondok, which specifically focuses only on the Al-Qur'an memorization program. The purpose of this research is to find out the Tikrar method used to memorize the Al-Qur'an, what factors support and hinder the Tikrar method, and how to overcome these obstacles. This qualitative research uses descriptive data, data collection is by interviews, observation and documentation, the analysis is descriptive. The results of the research show that: 1) The Tikrar method is used at the Al-Mubarok Islamic Boarding School in several stages, namely Bin-Nadhar, Tahfidz, Talaqqi, Tikrar, and Tasmi'. These stages consist of: (i) Tikrar Test, namely memorization Tikrar which is carried out to evaluate the quality of students' memorization of one juz every day; (ii) Joint Tikrar, namely memorizing Tikrar carried out with fellow students every day in the form of Tasmi' in pairs; and (iii) Exam Tikrar for Reciting Memories, memorization Tikrar in the form of Tasmi' (listening to) memorization to other students every multiple of five juz, and (iv) Tikrar Jam'iyyah Tahfidzul Qur'an, namely memorization Tikrar which is held every month with Pondok alumni Al-Mubarok Islamic Boarding School. At the Al-Mubarok Islamic Boarding School, the Tikrar method of memorizing the Qur'an is supported by three factors: (i) Motivation from oneself, parents, friends and the environment, (ii) Intention, and (iii) Sima'an ( Tasmi') in pairs. On the other hand, the things that hinder him are feeling lazy, weak in spirit, and forgetting verses that have been memorized. 3) To overcome the obstacles to the Tikrar method in memorizing the Qur'an at the Al-Mubarok Islamic Boarding School, this is by providing motivation to each other, listening to Murattal Al-Qur'an, reading books about the stories of memorizers of the Qur'an, getting support from those closest to you, and continue to try to memorize the Koran consistently.